Industrializable and sustainable approach for preparing extended-chain crystals of biodegradable poly(butylene succinate) and their applications. (3rd January 2019) - Ye, Hai-Mu; Chen, Xiao-Tong; Li, Hong-Fang; Zhang, Peng; Ma, Wenzhong; Li, Botian; Xu, Jun
Abstract: While polymer extended-chain crystals (ECCs) own promising physicochemical properties, effective product and application of ECCs is still challenging. Here, we develop an industrializable and sustainable production procedure process for ECCs of poly(butylene succinate) (PBS), which consists of a specially-designed melt mixing of the polymer and urea in internal mixer to produce inclusion complex and thereafter a washing step with water. The prepared ECCs show melting point at 137 °C and crystallinity higher than 90%, and the auxiliary materials, urea and water, can be recycled. The ECCs are further used as highly effective nucleating agent and reinforcer for commercial PBS, resulting in remarkable simultaneous increases in crystallization temperature, yield stress and elongation at break due to the perfect lattice matching and interfacial compatibility. Moreover, a shape memory material of single component of PBS has been fabricated with the in-situ addition of ECCs. Graphical abstract: Highlights: We have developed a sustainable approach for producing ECCs of polyesters. Industrializing production of ECCs is promising. ECCs were used to enhance crystallization and mechanical properties of matrix. A shape memory material of single component of poly(butylene succinate) was fabricated.